The Impact of Participative Leadership and Competencies on Performance of Village Fund Management - Anjung Pratama Putri; Winwin Yadiati (Universitas Padjadjaran, 2020)
The purpose of this study is to examine the effect of participative leadership and competencies on the performance of village fund management. The research subjects in this study are the village head and village apparatus on village governments in the Bandung Regency. The study involves 73 villages selected, adopting a simple random sampling technique. The data was obtained from respondents through a questionnaire instrument. Data were analyzed using descriptive statistical and multiple regression. The result indicates that participative leadership style of the village head and competencies of village apparatus is positively and significantly associated with the performance of village fund management.